Coopetitive tensions - Tidström, Annika (Routledge, 2018)
Coopetition naturally consists of a tension between cooperation and competition. Tensions in coopetition can be related to situations of conflict and conflict management. Significant elements of coopetitive tensions are the cause and the topic of tension, the management of tension, and the outcome of tension. Novel perspectives on coopetitive tensions are related to applying a dynamic, multilevel, and practice perspective.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|